Observational analysis of the variability of actions in judo: the key for success? - Marcus Fábio Agostinho; Emerson Franchini (Universidad de León, 2021)
The main objective of the present study was to determine whether variation in gripping action, actions before attacking, throwing techniques, direction of attack, transition from standing to groundwork combat, and groundwork techniques varied between male and female judo athletes and between gold, silver and bronze medalists in judo World Championships for cadet, junior and senior athletes. Therefore, 296 athletes who won medals in these competitions between 2018 and 2019, who executed a total of 1202 scoring actions in standing position and 300 scoring actions in the groundwork combat were analyzed. Higher variation was observed for gold medal winners for grip, actions before attack compared to bronze medalists, whereas transition variation was greater for gold medal winners compared to the other medalists. However, no differences were found between age groups, except when interacting with sex, as a lower technique variation was observed in female cadets compared to all other male age groups. Additionally, less variation was observed in females compared to males for grip, actions before attacking, number of techniques and direction of attacks. Therefore, variation in some elements can properly discriminate the podium position, females present less variation than males, but no relevant differences were found between age groups.